America again eaudiobook Re-becoming the greatness we never weren't. - Colbert, Stephen (2013)
Book store nation, in the history of mankind there has never been a greater country than America. You could say we're the #1 nation at being the best at greatness. But as perfect as America is in every single way, America is broken! And we can't exchange it because we're 236 years past the 30-day return window. Look around—we don't make anything anymore, we've mortgaged our future to China, and the Apologist-in-Chief goes on world tours just to bow before foreign leaders. Worse, the L.A. Four Seasons Hotel doesn't even have a dedicated phone button for the Spa. You have to dial an extension! Where did we lose our way?! It's high time we restored America to the greatness it never lost! Luckily, America Again will singlebookedly pull this country back from the brink. It features everything from chapters, to page numbers, to fonts. Covering subject's ranging from healthcare ("I shudder to think where we'd be without the wide variety of prescription drugs to treat our maladies, such as think-shuddering") to the economy ("Life is giving us lemons, and we're shipping them to the Chinese to make our lemon-flavored leadonade") to food ("Feel free to deep fry this book-it's a rich source of fiber"), Stephen gives America the dose of truth it needs to get back on track.